Respiratory Rehabilitation in the elderly, in the context of acute care: Systematic Review of Literature - Joana Alves; Eugénia Grilo (Associação Portuguesa dos Enfermeiros de Reabilitação, 2022)
Introduction: The multiorgan changes present in the aging process associated with a disease situation can intensify the functional decline and cause greater cardiorespiratory frailty. Objectives: Identify interventions likely to improve respiratory performance and functional capacity in elderly people in an acute setting. Methodology: Systematic literature review according to the Joanna Briggs Institute protocol through research in scientific articles databases by the EBSCOhost platform, including articles published from 2015 to 2021, using the Medical Subject Heading. Results: After the search, 144 articles were found, of which seven responded to the defined inclusion criteria. Four randomized clinical trials, two prospective quasi-experimental studies and one cross-sectional study were identified. Conclusion: According to the authors of the studies included in the literature review, respiratory rehabilitation interventions, such as the breathing control technique, the use of devices to train the respiratory muscles, allowed for a reduction in fatigue, an increase in effort tolerance, the improvement of lung volumes and capacities, with favorable results in functional performance.